PENGARUH MEDIA VIDEO PEMBELAJARAN VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP IPAS PESERTA DIDIK KELAS IV DI SD NEGERI 1 KRAMA JAYA - Maharani, Kartika; Syazali, Muhammad; Widiada, I Ketut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using animated video learning media on the understanding of science and natural science concepts of grade IV students at SD Negeri 1 Krama Jaya. This type of research is quantitative research with a quasi-experimental research design of the nonequivalent control group design type. The sampling technique used in this study is a non-probability sampling technique with a saturated sampling type. The data collection technique used is the test and observation technique. The hypothesis test used is the independent sample t-test. The results of the independent sample t-test obtained a t-count value> table, namely 3.066> 2.026 and a sig. (2-tailed) <0.05, namely 0.004 <0.05, which means that Ha is accepted and Ho is rejected. Based on the results of the study, it can be concluded that there is an effect of animated video learning media on the understanding of science and natural science concepts of grade IV students at SD Negeri 1 Krama Jaya.